Characteristics and properties of torrefied biomass pellets from Gmelina arborea and Dipterix panamensis at different times - Gaitán-Álvarez, Johanna; Moya-Roque, Róger (Revista Chapingo, Serie Ciencias Forestales y del Ambiente, 2016)
Torrefaction and pelletizing were studied in the generation of energy from lignocellulosic residues to increase the energy properties of the biomass. The aim of this study was torrefied sawdust from Gmelina arborea and Dipteryx panamensis at 200 °C in three time period: 0, 15 and 20 minutes. Then with the biomass, pellets of 6 mm diameter were manufactured and their physical properties, calorific value, density and compression force were evaluated. Both species had similar physical characteristics according to the average diameter (0.50 mm), length (21.50 mm), and water absorption rate (6.00 %). The calorific value increased from 9,749 kJ·kg-1 in un-terrified biomass to 18,126 kJ·kg-1 with torrefied biomass. The pellets from D. panamesis had greater density and compression force compared to G. arborea biomass. Based on the results, pellet compression force decreases as the torrefaction time increases. There is positive correlation between bulk density of pellets and compression force. The D. panamensis species has better torrefaction behavior and pelletizing than the wood of G. arborea.
Características y propiedades de pellets de biomasa torrefaccionada de Gmelina arborea y Dipterix panamensis a diferentes tiempos
Artículo científico
Keywords: Rayos X; Combustible; Compresión; Densidad; Residuos; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Agronomy